Differential M-ary orthogonal signaling for DS - Iossifides, A.C (IEEE Journal on selected areas in communications)
In this paper, we derive an analytical framework for the performance evaluation of an M-ary orthogonal scheme based on differential encoding/decoding of the Walsh/Hadamard chips prior/after spreading. This technique makes feasible nonpilot-assisted detection over fast fading environments such as the land mobile satellite (LMS) channel. Our results show that differential M-ary orthogonal signaling presents very good performance at Doppler frequency shifts much higher than the symbol rate. Amplitude statistics are considered to be Rayleigh, but may be easily extended to more general models based on the analytical derivation presented